Vilka strategier använder Nike sig av för att skapa identifikation i sin reklam på Instagram? - Broomé,Fredrika; Stenlund,Olivia (2026)
This essay examines how Nike uses narrative strategies in its commercials on Instagram to create identification with the recipient. The aim is to analyze how the visual, verbal and emotional interaction in the films contributes to building engaging stories that arouse emotional recognition and convey the brand's values. The study is based on Sonja Foss's model for narrative analysis, which enables an examination of the central parts of the story such as events, characters, conflicts and resolutions. The narrative analysis is combined with a multimodal perspective to see how image, sound, text and movement interact and in turn reinforce the rhetorical message. To distinguish identification, the study has also used Kenneth Burke's identification theory. Through this method, it is analyzed how Nike positions itself as a brand and how identification is created through emotional expressions, visual strategies and value-laden stories. The study in turn contributes to an increased understanding of how multimodal storytelling is used in digital marketing on social media, in this case Instagram videos.
Keywords: Advertising; Narrative; Identification; Multimodality; Visual analysis